First description of the egg ultrastructure of Chetogena scutellaris (Wulp, 1890) (Diptera: Tachinidae) - Pinheiro, Rodrigo A.; Toma, Ronaldo; Santos, Conceição A.; Soares, Marcus A. (Zootaxa, 2026)
N/A